Oriented 3D Magnetic Biskyrmions in MnNiGa Bulk Crystals. Issue 17 (13th March 2019) - Li, Xiyang; Zhang, Shilei; Li, Hang; Venero, Diego Alba; White, Jonathan S; Cubitt, Robert; Huang, Qingzhen; Chen, Jie; He, Lunhua; van der Laan, Gerrit; Wang, Wenhong; Hesjedal, Thorsten; et al.
Abstract: A biskyrmion consists of two bound, topologically stable, skyrmion spin textures. These coffee‐bean‐shaped objects are observed in real space in thin plates using Lorentz transmission electron microscopy (LTEM). From LTEM imaging alone, it is not clear whether biskyrmions are surface‐confined objects, or, analogous to skyrmions in noncentrosymmetric helimagnets, 3D tube‐like structures in a bulk sample. Here, the biskyrmion form factor is investigated in single‐ and polycrystalline‐MnNiGa samples using small‐angle neutron scattering. It is found that biskyrmions are not long‐range ordered, not even in single crystals. Surprisingly all of the disordered biskyrmions have their in‐plane symmetry axis aligned along certain directions, governed by the magnetocrystalline anisotropy. This anisotropic nature of biskyrmions may be further exploited to encode information. Abstract : Biskyrmion scattering is measured in a single‐crystalline centrosymmetric MnNiGa bulk sample using small‐angle neutron scattering. The biskyrmions are not long‐range ordered, and all of the disordered biskyrmions have their in‐plane symmetry axis aligned along certain directions, governed by the magnetocrystalline anisotropy. Such an anisotropic nature of biskyrmions, representing an extra degree of freedom, may be exploited as an information carrier.